Chromatographic Profiles of Umami Fractions from Indonesian Commercial Salty Soy Sauce - Hanifah Nuryani Lioe; Diana Ayu Nindita; Warsono El Kiyat (Indonesian Food and Nutrition Progress, 2019)
Salty soy sauce subjected in this study is a variety of commercial soy products in Indonesia. Chromatographic profiles linked to taste dilution analysis of the soy sauce were analyzed by Sephadex G-15 gel filtration chromatography followed by RP-HPLC. The results showed that there were 4 umami fractions (Fractions I − IV) obtained by Sephadex G-15 separation. Chromatographic profiles at 254 nm could show the differentiation of the four fractions and then their RP-HPLC profiles were proven to be different from each other. Fraction III which contained 65% of the soy sauce dry matters, had the highest umami intensity with umami TD factor of 256, meanwhile, this fraction was tasted salty due to the salt contained in the soy sauce. Fraction III was dominated by the later peaks in the RP-HPLC chromatogram, which was more hydrophobic. The hydrophobic components were commonly tasted bitter, perhaps in the commercial salty soy sauce, the taste interaction between the umami and bitter components might have occurred.